Differential object indexing in Bulgarian - The role of discourse prominence and predictability - Compensis, Paul (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
In this study, I argue that object reduplication in Bulgarian is a special encoding strategy that is concerned with discourse management and primarily used to mark (perceived) deviances from expectations with respect to the status of referents in discourse. In particular, I adopt a new perspective by capturing the phenomenon under discussion as a form of differential object marking with a person index, i.e., differential object indexing (DOI). Based on theoretical considerations, corpus evidence and a comprehensive empirical investigation, I reject the interpretation of Bulgarian DOI as a topic marker and suggest a functional explanation in terms of discourse prominence. In addition, I emphasize the role of predictability as a relevant dimension underlying this type of differential marking. I present evidence from acceptability judgment studies and web-based experiments suggesting that DOI in Bulgarian is typically used to (re-)activate or clarify the discourse prominence status of a less prominent referent. In terms of processing, I present the results from an ERP experiment and a visual cueing web-experiment showing that the presence of an object index during online processing modulates (discourse-based) expectations, initiates discourse updating and interacts with (visually induced) salience of a referent. Throughout this study, I elaborate on the association of discourse prominence and language-related predictability with more general cognitive mechanisms, such as attention and prediction
Keywords: Differential object indexing; Object agreement; Bulgarian; Psycholinguistics; Neurolinguistics; Discourse prominence; Prominence in language; Prediction in language; Predictability; Differential object marking